Recent updates on victimology and its influence on criminal justice system - Gopalan, Rejani Thudalikunnil (Victimology, 2022)
This introductory chapter aimed to provide the historical development of the field of victimology and its present and future scenario. In specific, the chapter covered definitions of victimology and the history of the development of victimology as a special area. Types of victimology, various theories, and perspectives of victimology were elaborated. Victim precipitation theory, lifestyle and exposure theory, routine activities theory, deviant place theory, social learning theory, control balance theory and general theory of crime were described in detail. Also, various risk factors/biopsychosocial factors associated with victimization have been discussed. Most of the theories are limited with a focus on one or few aspects of crime, victims and offender. As the crime itself is complicated with multifactorial aspects, future studies can focus on the same to explain and propose theories more comprehensively. It is important to continue to develop and implement standard international protocols on the rights of victims and abuse of power and to influence the criminal justice system across the world.